2015
DOI: 10.5713/ajas.15.0576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Furnished Cage Type on Behavior and Welfare of Laying Hens

Abstract: This study was conducted to compare the effects of layout of furniture (a perch, nest, and sandbox) in cages on behavior and welfare of hens. Two hundred and sixteen Hyline Brown laying hens were divided into five groups (treatments) with four replicates per group: small furnished cages (SFC), medium furnished cages type I (MFC-I), medium furnished cages type II (MFC-II), and medium furnished cages type III (MFC-III) and conventional cages (CC). The experiment started at 18 week of age and finished at 52 week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
(30 reference statements)
0
13
2
1
Order By: Relevance
“…In the current study, resting behaviours including both resting and laying in hens housed in conventional cages were highly expressed compared to those of housed in furnished cages. Different from our statements, Li et al, (2016) observed no significant difference between hens housed in furnished cages and conventional cages. On the other hand Pohle andCheng, (2009), Meng et al, (2017) stated higher sitting activity in hens housed in conventional cages.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In the current study, resting behaviours including both resting and laying in hens housed in conventional cages were highly expressed compared to those of housed in furnished cages. Different from our statements, Li et al, (2016) observed no significant difference between hens housed in furnished cages and conventional cages. On the other hand Pohle andCheng, (2009), Meng et al, (2017) stated higher sitting activity in hens housed in conventional cages.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, Shimmura, et al, (2007) reported that, furnished cages do not have any influence in comfort behaviours. Unlike us Li et al, (2016) reported that furnished cages increased comfort behaviours. It is probably not enough that only the cages are furnished, the size of the cages is also influential.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations